Inovasi Teknologi untuk Pengembangan Jagung dalam Rangka Mendukung Ketahanan Pangan dan Energi - Wawan Hermawan; Roh santoso; Tjahja Muhandri; Titi Candra Sunarti (Jurnal Ilmu Pertanian Indonesia, 2012)
Recent researches resulted several innovations such as an integrated machine for planting and fertilizer application for corn cultivation, corn noodle production, and delignification process of corn stover. The objectives of this research were (1) to improve working performances of the first prototype of integrated machine for tillage, planting, and fertilizer application for corn cultivation, (2) to develop an automatic irrigation system using solar energy, (3) to optimize processing variables on corn noodle production, and (4) to explore the delignification process of corn stover to improve the enzymes susceptibility in saccharification process. The planting and fertilizer application machine for corn cultivation has been successfully modified and showed better working performance. An automatic irrigation system using solar energy for corn cultivation has been arranged using a solar panel, a water pump, a battery, and a controlling system. The pumping discharge from a 10 m depth of well was 0.1 l/s. The optimum processing condition was resulted from the combination of 80% dough’s moisture content, at 90 °C extruder temperature and 75 rpm screw speed. The microwave heating treatment could destruct and solubilize the lignin, as compared to chemical and hydrothermal processes, and reduced the fiber crystallinity.